Feedback on Formative Assessments in Undergraduate Medical Education of Bangladesh (Bangladesh Journal of Physiology and Pharmacology, 2010)
The study was conducted to examine the extent and methods of giving feedback by teachers after the formative assessments to the undergraduate medical students of Bangladesh.This descriptive study was conducted in four purposively selected medical colleges of Dhaka. Views of 174 teachers and 332 students were collected through self-administered semi-structured questionnaires for this purpose.It was found that majority of the teachers perceived that through feedback students find out their weaknesses and thereby can perform better in future. It was also found that feedback was not given in most of the cases by the teachers to their students. The methods of giving feedback were not perfect all together.To ensure feedback after the formative assessments teachers should be motivated and trained up and it should be mentioned in the curriculum that feedback is mandatory. Key words: Formative assessment; Feedback; Medical education of Bangladesh; Assessments in medical education; Undergraduate curriculum Bangladesh. DOI: 10.3329/bjpp.v25i1.5741Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 18-22